Simulation and experimental investigation of a wide band PZ MEMS harvester at low frequencies - Salim M.D.; Salleh H.; Salim D.S.M. (2023)
A commercial brass reinforced PZ bimorph cantilever of the type 5H4E was simulated using COMSOL FEM software and then a serious of experimental tests were carried out in a vibration laboratory using a labview of NI make as instrumentation and control system. By using a shaker the cantilever was vibrated and set into acceleration of 0.25 g rms during all stages as this value was considered to be available and acceptable in balanced large rotating machines in industry. Field vibration spectrum analysis was carried out in a power station confirmed that. A band of frequencies ranging from 30 to 109 Hz was experimentally tested by using different perforated steel shims as a proof mass at the end of the cantilever. Values of 63 lW/cm3 at a frequency of 33 Hz for power density, 187 lW for max power, 14.8 V for max OCV, and 8.26 V for max, on load voltage, were obtained. Frequency resolution of 1 Hz was experienced. Trends of the results obtained experimentally and through simulation were comparable. 2012 Springer-Verlag.